Нова концепція розвитку України - Білопольский, М.Г. (Вісник економічної науки України, 2023)
Зроблено критичний аналіз та огляд стану економіки України за роки незалежності. Проаналізовано вплив іноземних консультантів та радників. Зроблено висновок про неефективність зроблених політичних рішень. Запропоновано деякі шляхи покращення існуючого стану. A critical analysis and review of the state of Ukraine’s economy during the years of independence was made. The impact of foreign consultants and advisors is analyzed. A conclusion was made about the ineffectiveness of the political decisions made. Some ways to improve the current state are proposed.